An e-Business Logistic Model in Taiwan - Lin, Edward; Chen, Ming-Kuen; Jiang, Wei-Chi (Journal of Comparative International Management)

(untitled) (Management Futures, 2006)
The current article develops a framework for an e-business logistic model in Taiwan. The model includes e-marketplace, logistic, organization, and informational systems factors. Data used for this research come from a survey of business groups, including marine and air carriers, terminal warehousing, custom brokers, shipping centers, and marine information service providers. Our study reveals relationships between essential variables for e-business trading in the logistic industry. These include organizational advantage and information technology, strategy and vision, consumer-directed service and planning, lower cost and high quality customer service, quick merchandise delivery and low inventory, and long-term development plans. Specifically, we found that the logistic industry in Taiwan ignores the details of purchasing procedure in e-marketplace operation, focusing more on actual merchandise delivery, consumer satisfaction, and downstream consumer service. In addition, the logistical industry in Taiwan also involves employee adjustment to the new environment, support from upper management, training and, application of information technology.